Symbiosis : an introduction to biological associations - Paracer, Surindar (Oxford University Press, 2000)
1. Introduction. 2. Viral Symbiotic Associations. 3. Bacterial Associations of Bacteria, Protozoa, and Animals. 4. Bacterial Pathogenesis: Molecular Mechanisms. 5. Bacterial Associations of Plants. 6. Symbiosis and the Origin of the Eukaryotic Cell. 7. Fungal Associations of Protozoa and Animals. 8. Fungal Associations of Fungi, Algae, and Plants. 9. Parasitic and Mutualistic Protozoans. 10. Photosynthetic Associations of Protozoans and Invertebrates. 11. Animal Parasitism: Flukes, Tapeworms, Nematodes, and Parasitoids. 12. Flowering Plant Symbioses. 13. Behavioral and Social Symbioses. 14. Sy.